The Use of Prambanan Temple as a Source of History Learning for Tadris IPS IAIN Kudus Students - Karina Puji Lestari; Ida Rahmawati; Siti Nor Kholisoh; Laily Fu’adah; Moh. Rosyid (JURNAL PENDIDIKAN IPS, 2024)
Learning history in the classroom, which tends to be monotonous and boring, leads to a decline in students' understanding of the material presented. This issue needs attention and innovative learning approaches, such as direct learning from historical sources through Field Work activities. The aim of this research is to assess the utilization and relevance of Prambanan Temple as a historical learning resource for students of Tadris IPS at IAIN Kudus. This study employs a qualitative approach with a descriptive method. Data collection techniques include data gathering, data reduction, data presentation, and conclusion drawing. The research findings indicate that Prambanan Temple is appropriate and relevant as a historical learning resource because it aligns with the Indonesian Cultural History course in the 4th semester, specifically the subchapter on Hinduization: Religion, Language, Literature, Architecture, Sculpture, and Relief, which explains how Hinduism entered Indonesia, the society of that era, and the architectural style used in the creation of temple reliefs. Additionally, learning through fieldwork can provide students with a more holistic, contextual, and memorable learning experience, enhancing their understanding and pride in national cultural heritage.